CONFLICTS BETWEEN FORESTRY AND AGRICULTURAL LAND – USES IN OGUN STATE (2012)
Clash of interests between custodians of government Forest Reserves (FRs) in Ogun State and farmers operating within them, often results in conflicts causing disruption of socio-economic activities and sometimes loss of lives. Information on the causes and effects of these clashes would better inform policy makers and forestry professionals on workable and sustainable land-use practice. Therefore, factors responsible for such conflicts and their effects were investigated. Seven hundred and fifty farmers were randomly selected based on probability proportionate to size from 72 enclaves. This represents 30% of the total number of enclaves in the nine FRs in the State. In addition, 30% of staff of Ministries of Forestry and Agriculture (72 and 32 respectively) were randomly selected for questionnaire administration. Furthermore, 30% (32) of the timber contractors operating within the FRs were randomly selected for interview using an interview schedule. Data were collected on existence, causes and effects of conflicts, land hunger, accessibility to forestland and farming systems practised. Secondary data on the thrust of subsisting forestry and agricultural policies were obtained from the State Agricultural Policy, Federal land-use Act of 1978 and reports from the State Ministry of Forestry. Data were analyzed using descriptive statistics and logit model at p<0.05. Among the farmers, descriptive statistics revealed that 74.3% had unauthorized access to FRs, 68.1% were resident within FRs while 55.4% utilized lands approved by government for farming. Furthermore, 68.7% of the farmers identified taungya system and shifting cultivation as the prevalent farming systems practised. An average of two forest land encroachment cases were reported at each of Arakanga and Edun stream FRs yearly in the last 10 years while an average of 24 forest land encroachment cases was reported yearly in the last 10 years in Omo FR. Also, results of logit regression analysis revealed that the location of FRs where farmers operate (odds ratio = 2.39), rights of farmers to use forestland for farming (odds ratio = 2.19) and farm size (odds ratio = 1.52) are factors that are likely to cause conflicts over the use of forest lands in Ogun state. Furthermore, descriptive analysis of timber contractors‟ response revealed that, 72.6% identified destruction of cash crops during timber exploitation as cause of conflicts between them and farmers. State Ministries of Forestry and Agriculture officials identified loss of forests (27% and 25.2%), species (25.5% and 24%) and lives (22.5% and 22%), as effects of conflicts in the FRs. The thrust of the extant agricultural land-use policy made no provision to UNIVERSITY OF IBADAN LIBRARY iv penalize forestland encroachers. Conflicts in the use of forest land ensued between farmers and timber contractors on one hand and farmers and forest custodians on the other. The existence of land hunger in the forest reserves host communities, unauthorized access to forest land and absence of provision for penalty in the extant agricultural land use policy for forest encroachers encouraged activities engendering conflicts over the use of forest land. Keywords: Land-use conflicts, Forest policy, Forest reserves, Land hunger Word count: 481